2022
DOI: 10.1021/acssensors.2c01597
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive NO Sensor Based on a Nickel Single-Atom Electrocatalyst for Preliminary Screening of COVID-19

Abstract: A new coronavirus, SARS-CoV-2, has caused the coronavirus disease-2019 (COVID-19) epidemic. A rapid and economical method for preliminary screening of COVID-19 may help to control the COVID-19 pandemic. Here, we report a nickel single-atom electrocatalyst that can be printed on a paper-printing sensor for preliminary screening of COVID-19 suspects by efficient detection of fractional exhaled nitric oxide (FeNO). The FeNO value is confirmed to be related to COVID-19 in our exploratory clinical study, and a mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…[3][4][5] Moreover, some studies have shown that FeNO level is a predictor of COVID-19 disease severity. [6][7][8][9] Obviously, the detection of ppb-level nitric oxide (NO) has its unique credit in the clinical diagnosis of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Moreover, some studies have shown that FeNO level is a predictor of COVID-19 disease severity. [6][7][8][9] Obviously, the detection of ppb-level nitric oxide (NO) has its unique credit in the clinical diagnosis of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,31 However, few studies have been reported on the design of SACbased electrochemical sensors. [32][33][34] Furthermore, the active site of natural ascorbate peroxidase has been characterized as a central iron ion coordinated by the four pyrrole nitrogen atoms, 35,36 yet the design of SACs to mimic such structures with desirable activity remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that human saliva also contains NO in nano-micromolar levels. , Oral bacteria and salivary glands play a major role in the conversion process of NO from nitrate (NO 3 ) or nitrite (NO 2 ) in the salivary fluid. Any increase and decrease in the NO level in saliva can cause several deadly diseases including ischemia, hypertension, Parkinson, myocardial infarction, and cancer. Oral diseases like periodontitis are also linked to higher NO concentrations in saliva …”
Section: Introductionmentioning
confidence: 99%